Effect of Pneumoperitoneum and Lateral Position on Oropharyngeal Seal Pressures of Proseal LMA in Laparoscopic Urological Procedures - Rustagi, Preeti (J Clin Diagn Res, 2017)
INTRODUCTION: A sustained and effective oropharyngeal sealing with supraglottic airway is required to maintain the ventilation during laparoscopic surgery. Previous studies have observed the Oropharyngeal Seal Pressure (OSP) for Proseal Laryngeal Mask Airway (PLMA) after pneumoperitoneum in supine and trendelenburg position, where PLMA was found to be an effective airway device. This study was conducted with ProSeal LMA, for laparoscopic Urologic procedures done in lateral position. AIM: To measure OSP in supine and lateral position and to observe the effect of pneumoperitoneum in lateral position on OSP. Secondary objectives were to assess adequacy of ventilation and incidence of adverse events. MATERIALS AND METHODS: A total number of 25 patients of American Society of Anaesthesiologists (ASA) physical status II and I were enrolled. After induction of anaesthesia using a standardized protocol, PLMA was inserted. Ryle’s tube was inserted through drain tube. The position of PLMA was confirmed with ease of insertion of Ryle’s tube and fibreoptic grading of vocal cords. Patients were then put in lateral position. The OSP was measured in supine position. This value was baseline comparison for OSP in lateral position and that after pneumoperitoneum. We assessed the efficacy of PLMA for ventilation, after carboperitoneum in lateral position (peak airway pressure, End Tidal Carbon dioxide (EtCO(2)), SPO(2)). Incidence of adverse effects (displacement of device, gastric insufflation, regurgitation, coughing, sore throat, blood on device, trauma) was also noted. RESULTS: The OSP was above Peak Airway Pressure (PAP) in supine (22.1±5.4 and 15.4±4.49cm of H(2)O) and lateral position (22.6±5.3 and 16.1±4.6). After pneumoperitoneum, which was in lateral position, there was statistically significant (p-value <0.05) increase in both PAP (19.96±4.015) and OSP (24.32±4.98, p-value 0.03). There was no intraoperative displacement of PLMA. There was no event of suboptimal oxygenation. EtCO(2) was always within normal limits. Gastric insufflation was present in one patient. One patient had coughing and blood was detected on device. Three patients had throat discomfort post-operatively. CONCLUSION: In this study, Oropharyngeal seal pressures with PLMA were found to increase after pneumoperitoneum in lateral position. PLMA forms an effective seal around airway and is an efficient and safe alternative for airway management in urological laparoscopic surgeries done in lateral position.